(untitled) - Gyde, Kathy (Oxford, 1997)
The Teacher's book contains: background notes on the texts, teaching notes on procedure, optional activities, transcripts of the listening texts, a full answer key including outlines of summaries and composition tasks, and photocopiable tests
Keywords: English language,English language; Study and teaching,Textbooks for foreign speakers